2015
DOI: 10.1055/s-0034-1396321
|View full text |Cite
|
Sign up to set email alerts
|

Mycosporine-Like Compounds in Chlorolichens: Isolation from Dermatocarpon luridum and Dermatocarpon miniatum, and their Photoprotective Properties

Abstract: !Two mycosporines were isolated for the first time in two chlorolichen species, Dermatocarpon luridum and Dermatocarpon miniatum. Mycosporine glutaminol (1) and mycosporine glutamicol (2) were isolated along with the ethyl ester of mycosporine glutamicol (3), which was formed during the purification process. Aqueous extracts and pure mycosporines were then investigated for their antioxidant activities and photoprotective properties along with their photostability and photocytotoxicity. Semi-purified mycosporin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In a recent study, oxo-mycosporines from a chlorolichens were described (Nguyen et al 2015). This finding may suggest revision of the concept of a MAA occurrence specifically related to presence of cyanobacteria (La Barre et al 2014).…”
Section: Resultsmentioning
confidence: 89%
“…In a recent study, oxo-mycosporines from a chlorolichens were described (Nguyen et al 2015). This finding may suggest revision of the concept of a MAA occurrence specifically related to presence of cyanobacteria (La Barre et al 2014).…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, careful observation of the 1 H NMR spectrum indicated that there were some minor peaks belonging to the minor compound (Z)-nostodione A [5], and the integrations of some protons indicated that the ratio of the E/Z isomers was 9/1. Up to now, nitrogen-containing compounds from lichens was very rare with reports of several compounds [1,11] and only one nitrogen-containing compound, a cyclopeptide was found in the Roccella genus [12]. This was the first time alkaloid 5 was reported as a lichen metabolite.…”
Section: Resultsmentioning
confidence: 99%
“…Except for compound 1, other compounds were reported for the first time in D. luridum. In the previous work, the authors have shown that mycosporine 1 has a strong absorption at 310 nm in the region of UVB (290-320 nm) with high ε 12540 M -1 .cm -1 suggesting the potential application as a natural photoprotectant [4]. Such compound contains one acido-basic site, however, its dissociation constant has never been published so far.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that instead of containing common lichen subtances as phenolic compounds, dibenzofuranes, depsides, depsidones, quinones, pulvinic acid derivatives etc., lichen species belonging to genus Dermatocarpon included several sugar alcohols as mannitol, sorbitol, volemitol and arabitol [2,3]. The first report on the occurrence of mycosporine glutaminol in the aqueous extract of D. luridum [4] prompted us that a phytochemical study on such lichen could be useful for chemical taxonomy. Recently, mycosporines have received much attention for their putative role in UV photoprotection.…”
Section: Introductionmentioning
confidence: 99%